Injection moulding and thermal properties of polypropylene hinges - Othman, Mohd Hilmi (2008)
Studies about polypropylene thermal properties have been carried out towards 2- cavities test mould of an integral hinge and tension band sample. This mould was fitted with pressure /temperature transducer and adapted with a data acquisition system. By using both injection moulding practical work and MoldFlow Plastic Insight (MPI) simulation, the predictions and accuracy of in-mould temperature have been carried out with different settings of processing parameters such as screw speed, shot size, mould temperature and barrel temperature profile. These thermal properties analysis were very important in order to produce optimum processing parameters and a better quality with longer life span of hinges and tension band which are widely applied to product packaging. The analysis of results showed that the measured in-mould temperature during injection moulding practical produced the correct trend as referred to the rheological theories of polypropylene. Through simulation process, MPI has predicted the same trend and slightly similar in-mould temperatures as compared with data acquisition from injection moulding practical work. For additional findings, the shot size of sample can be minimised, with the elimination of second screw speed during packing time. This reduction may helps to accelerate injection cycle time and reduced material consumption. Finally, the optimum process parameter settings for hinge and tension band sample have been rectified and verified by both simulation and practical work. It is proven that simulation prediction able to produce beneficial results which may contribute to make improvements in terms of numbers of trials and procedures, times / power / energy consumption and type of materials which have been used during hinge and tension band design and production.